Anatomical organization of the brain of a diurnal and a nocturnal dung beetle. Issue 8 (10th March 2017) - Immonen, Esa‐Ville; Dacke, Marie; Heinze, Stanley; el Jundi, Basil
Abstract: To avoid the fierce competition for food, South African ball‐rolling dung beetles carve a piece of dung off a dung‐pile, shape it into a ball and roll it away along a straight line path. For this unidirectional exit from the busy dung pile, at night and day, the beetles use a wide repertoire of celestial compass cues. This robust and relatively easily measurable orientation behavior has made ball‐rolling dung beetles an attractive model organism for the study of the neuroethology behind insect orientation and sensory ecology. Although there is already some knowledge emerging concerning how celestial cues are processed in the dung beetle brain, little is known about its general neural layout. Mapping the neuropils of the dung beetle brain is thus a prerequisite to understand the neuronal network that underlies celestial compass orientation. Here, we describe and compare the brains of a day‐active and a night‐active dung beetle species based on immunostainings against synapsin and serotonin. We also provide 3D reconstructions for all brain areas and many of the fiber bundles in the brain of the day‐active dung beetle. Comparison of neuropil structures between the two dung beetle species revealed differences that reflect adaptations to different light conditions. Altogether, our results provide a reference framework for future studies on the neuroethology of insects in general and dung beetles in particular. Abstract : Using immunohistochemistry, confocal imaging and 3D modelling, the authors describe the neuropils and major fiber bundles in the brain of a diurnal and nocturnal dung beetle species. Comparison of major neuropils reveals differences reflecting adaptations to different light conditions.